Dessiner la campagne pour dessiner la ville - Jennifer Buyck (Projets de Paysage)
The sense of landscape into the Schemes of Territorial Coherence (Scot) – main tools of the french and contemporaneous system of spatial anticipation – caught here our attention. In such a framework, landscape revealed itself as a recurrent issue of such projects. The Scot of metropolitan areas do not escape from this tendency and three of this approaches, both representative and innovative in relation to the others, were selected in order to lead a more detailed analysis of the role played by landscape. The latter, permitting the reunion of the major landscape’s paradigms, legitimated the creation of a main notion, an active complex, resulting in the reformulation and the putting in coherence of the projects’ objectives. Moreover, it seamed to us that this metropolitan creation through landscape wasn’t without repercussions on the relations between urban and rural.